Comparative study of fetomaternal outcome in adolescent and young adult primigravidas - Meherda, Kanti; Mathur, Shikha (International Journal of Research in Medical Sciences, 2017)
Background: Adolescent pregnancy is a worldwide public health problem. WHO has defined adolescence as the period from 10-19 years of age. Purpose of the study was to compare the fetomaternal outcome in adolescent and young adult primigravidas. Methods: The study was conducted at a tertiary care centre over a period of six months. 150 adolescent (in our study between 15-19 years of age) and 150 young adults (20-25 years) primigravidas who delivered at our institution were randomly selected for the study. All the data including age, booking status, educational and economic status and address were noted. All essential antepartum, intrapartum and postpartum data were collected for both the groups and compared using Chi square test. Results: In our study the incidence of antepartum, intrapartum and postpartum complications was 86%,36% and 10% respectively in the study group. But in the control group only 40% of the subjects had antepartum complications ,17.33% had intrapartum complications and the incidence of postpartum complications was only 4%. The difference is highly significant with a p value <0.001. Conclusions: Adolescent pregnancy is associated with adverse fetomaternal outcome and any effort to prevent it is worthwhile.